Employment rights of refugees under the 1951 Convention relating to the status of refugees - Eishan Jan, Mohammad Naqib; Ali Mohamed, Ashgar Ali; Ahmad, Muhamad Hassan (Moment Publications, 2018)
The 21st Century is shockingly witnessing the growing trends of stateless, vulnerable and persecuted people around the world. Albeit the 1951 Convention relating to the Status of Refugees (1951 Convention) and its 1967 Protocol Relating to the Status of Refugees (1967 Protocol) offer numerous legal basis for the protections of refugees, these are still seemed inadequate to address the global plights of refugees. One of the problems associated with refugees is unemployment while seeking refuge in the host State. Surviving in a foreign country without a proper mean to earn a living often compels them to indulge in illegal activities which may inevitably affect the national security of the host nation. Hence, it is essential to guarantee employment rights to the refugees for their survivals. Thus, this paper generally intends to examine major legal provisions dealt with the employment of refugees under the 1951 Convention. In this paper, it is observed that most of the States nowadays are reluctant and not very much forthcoming in welcoming refugees let alone employing them. In fact, there are many benefits that a host State can gain from allowing refugees to work while they are living it its territory, namely, promoting the living standard of refugees in its jurisdiction, integrating them well in to the host society, and boosting the national economy, among others